210Pbxs. is a viable alternative to 137Cs for tracing soil redistribution in mountain pastures affected by heterogeneous Chernobyl fallout. Issue 4 (18th December 2022) - Baccolo, Giovanni; El Khair, Davide Abu; Nastasi, Massimiliano; Sisti, Monica; Ferrè, Chiara; Alewell, Christine; Comolli, Roberto
Abstract: Soil mobilization has been investigated by means of fallout radionuclides (FRN) in a first‐order catchment of the Eastern Alps. Caesium‐137, 210 Pbxs. ( 210 Pb excess or unsupported fraction), and 241 Am have been measured in soil samples collected from a pasture at about 2150 m above sea level. Combining pedological and radioactivity data, including mineral‐related radionuclides (primordial 40 K and nuclides belonging to the 232 Th and 238 U decay chains), the distribution of FRNs, their spatial variability, vertical distribution, and relationships with pedological and topographical variables were assessed. Because of low activity concentration, it was not possible to use artificial long‐lived 241 Am as a soil tracer, but preliminary results are encouraging. Inventories of 210 Pbxs. and 137 Cs have been converted into soil mobilization rates applying the MODERN model. Despite the gentle steepness and the absence of evident signs of erosion, the slopes of the considered catchment are affected by erosion at a rate up to 6 t ha −1 yr −1, likely related to grazing. A comparison between 210 Pbxs. and 137 Cs has revealed that at this site 137 Cs, the most used FRN for estimating soil redistribution, is not suitable for this purpose, probably due to its irregular spatial distribution on snow‐covered ground after the Chernobyl accident. Conversely, 210 Pbxs., owing to its continuous input, has provided reliable estimates of soil redistribution rates, in accordance with local morphology. The latter has in fact been related to morphometric variables in a regression model to provide an overview of soil erosion/sedimentation across the entire catchment, confirming that 210 Pbxs. is a viable alternative to trace soil erosion and deposition where the Chernobyl fallout occurred on snow‐covered ground. Abstract : This work deals with the application of fallout radionuclides to trace soil erosion and deposition at a high‐elevation pasture in the Eastern Alps. Artificial 137 Cs, the radionuclide most used for this purpose, is not suitable because of its irregular distribution on snow‐covered ground after the Chernobyl accident. In such contexts natural 210 Pbxs. provides reliable estimates of soil redistribution rates, being less affected by snow‐related processes. The possibility of exploiting artificial 241 Am has also been explored, with encouraging preliminary results.